Health education: social representation and everyday act of health professionals - Teixeira, Elizabeth; Costa e Silva, Bruna Alessandra; Pinto Fonseca, Jacquellyne; Martins de Sousa, Yasmin; Barros Machado, Larissa Cristina; de Castro Portal, Lorena; Lameira da Costa, Pollyana Thays; Castelo de Albuquerque, Nahima (O Mundo da Saúde, 2015)
Education and health are fields of production and application of knowledge for human development. The aim of this study is to understand the structure of social representations of health professionals on health education and identify educational practices performed by them in specialized reference units of the Secretary of State Public Health of the city of Belém. This is a descriptive and exploratory study guided by the Theory of Social Representations. The subjects were 56 health professionals from five units of reference and a health center in Belém, Pará. The analysis was through descriptive statistics Program Excel 2007; the data obtained was processed by Evoc 2003. The centrality of the social representation is based on prevention by means of orientation, aiming at quality of life and health. The everyday practices are based in individual orientations on the offices of the health professionals facing to the specialties of care of these institutions.